Sistem Diagnosis Penyakit pada Kambing Menggunakan Metode Forward Chaining (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2017)
Goats are ruminants and grazers. In cultivating goats, the average goat owners have less knowledge in terms of diseases that attack their domestic goats. Expert systems began to be used to help an expert or expert in diagnosing disease in goats based on existing symptoms. Objectives and benefits of Diagnosis goat disease, among others, is to facilitate and accelerate knowing the type of disease that attacks the goat. To determine the diagnosis of goat disease, researchers create expert system by applying forward chaining method. Diagnose goat disease using Forward Chaining method. In this study the types of diseases that can be diagnosed as much as 16 diseases. Testing used is the test of accuracy with test data of 16 diseases with an accuracy rate of 100%. The conclusion of the research that has been done based on the problems that have been resolved through the manufacture of this expert system is expert system to determine goat disease designed with rule base and forward chaining method. The number of rules used as many as 16 rules with 43 types of questions in accordance with the number of symptoms.